Geoglossum subdifforme sp. nov. and G. simile, Two New Earth Tongues from South Korea - Chang Sun Kim; Young-Nam Kwag; Dae Ho Kim (Mycobiology)
During an investigation of Korean Ascomycetes in 2023, we found two undescribed species from South Korea. We analyzed them using a combined approach, including morphological and phylogenetic analyses of the rDNA regions (internal transcribed spacer and large subunit). The two species were identified to belong to the genus Geoglossum; the species G. simile and a new species named G. subdifforme sp. nov. The phylogenetic tree constructed using the ITS region showed that G. subdifforme is closely related to G. difforme. These species are distinguishable by certain morphological characteristics, particularly the size and septae of ascospores. Morphologically, G. simile is related to G. glabrum, but it is distinguishable by the morphological characteristics of paraphyses as well as ITS sequences. In this study, the descriptions, photographs, and phylogenetic relationships of these Geoglossum species are presented.